Effect of chaotropes on the kinetics of iron release from ferritin by flavin nucleotides - Johnson, Lindsay E.; Wilkinson, Tyler; Arosio, Paolo; Melman, Artem; Bou-Abdallah, Fadi (Biochimica et biophysica acta, 2017)
Ferritins are ubiquitous multi-subunit iron storage and detoxification proteins that play a critical role in iron homeostasis. Ferrous ions that enter the protein's shell through hydrophilic channels are rapidly oxidized at dinuclear centers on the H-subunit before transfer to the protein's cavity for storage. The mechanisms of iron loading have been extensively studied, but little is known about iron mobilization. Fe(III) reduction can occur via rapid reduction by suitable reducing agents followed by chelation of Fe(II) ions or via direct and slow Fe(III) chelation. Here, the iron release kinetics from ferritin by FMNH2 in the presence of various chaotropic agents are studied and their in-vivo physiological significance discussed. The iron release kinetics from horse and human ferritins by FMNH2 were monitored at 522nm where the Fe(II)–bipyridine complex absorbs. The experiments were performed in the presence of different concentrations of three chaotropic agents, urea, guanidine HCl, and triton. Under our experimental conditions, iron reductive mobilization by the non-enzymatic FMN/NAD(P)H system is limited by the concentration of FMNH2 and is independent on the type or amount of chaotropes present. Diffusion of FMNH2 through the ferritin pores is an unlikely mechanism for ferritin iron reduction. An iron mobilization mechanism involving rapid electron transfer through the protein shell is discussed. Caution must be exercised when interpreting the kinetics of iron mobilization from ferritin using the FMN/NAD(P)H system. The kinetics are highly dependent on the amount of dissolved oxygen and the concentration of reagents used. •Chaotropes do not affect rates of iron mobilization from ferritin by FMNH2.•The rates of iron release from ferritin are heavily dictated by molecular oxygen.•Flavin mononucleotide cannot diffuse through ferritin pores to reduce the iron core.•Iron mobilization by FMNH2 likely involves electron transfer via the ferritin shell.